The The Implementation of the Learning Organization Concept in Improving the Quality of Teacher Professional Organization - Leny Sri Wahyuni; Hanafiah; Sofyan Sauri (Ilmu Inovasi Nusantara, 2023)
This study aims to describe and analyze the implementation of the learning organization concept to improve teacher professional organizations' quality. This research is qualitative research using case studies. The data collection was carried out through documentation studies, interviews, and observations. Based on the results of the research, it is known that the concept of a learning organization can be an alternative approach to improve the quality of professional teacher organizations so that they can adapt to various changes and become competitive and independent organizations in the global era. The West Java Nahdlatul Ulama Teachers Association (PW. Pergunu) organization feels this. PW. Pergunu West Java is improving the quality of its organization (continuous improvement) by implementing the five disciplines of the learning organization, namely increasing personal mastery through bachelor, master and doctoral scholarship programs, training and seminars, teacherpreneur, and publishing the ASWAJA journal; Shared vision is carried out through the formulation of vision and mission as well as outreach to its realization on various occasions and momentum, such as during work meetings; Mental models are built through program evaluation and coordination during regional coordination meetings; Team learning is implemented through Focus Group Discussions; meanwhile the concept of system thinking is applied to create good organizational governance